2017
DOI: 10.3174/ajnr.a5143
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Cortical Glutathione Levels, Brain Amyloidosis, and Memory in Healthy Older Adults Investigated In Vivo with1H-MRS and Pittsburgh Compound-B PET

Abstract: Background and Purpose Oxidative stress has been implicated as an important pathological mechanism in the development of Alzheimer’s disease (AD). The purpose of this study was to assess whether glutathione (GSH) levels, detected noninvasively with proton magnetic resonance spectroscopy (1H MRS), are associated with brain amyloidosis and memory in a community-dwelling cohort of normal older adults. Materials and Methods Fifteen cognitively normal subjects were prospectively enrolled in this study. All subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 54 publications
0
44
0
Order By: Relevance
“…As described above, enhanced generation of reactive oxygen species is a typical phenomenon of AD and has been attributed to decreased levels of the brain antioxidant, glutathione [ 31 ]. Moreover, lowered cortical glutathione levels were found as a biomarker of early Alzheimer disease pathogenesis [ 32 ]. However, in CL2006, the knockdown of gcs-1 , encoding the rate-limiting enzyme for glutathione synthesis, did neither affect the paralysis rate nor did it prevent betaine from being active in diminishing paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, enhanced generation of reactive oxygen species is a typical phenomenon of AD and has been attributed to decreased levels of the brain antioxidant, glutathione [ 31 ]. Moreover, lowered cortical glutathione levels were found as a biomarker of early Alzheimer disease pathogenesis [ 32 ]. However, in CL2006, the knockdown of gcs-1 , encoding the rate-limiting enzyme for glutathione synthesis, did neither affect the paralysis rate nor did it prevent betaine from being active in diminishing paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance spectroscopy has been used to demonstrate decreased GSH levels in AD patients (Mandal, Saharan, Tripathi, & Murari, 2015). GSH has also been shown to be associated with amyloid load in cognitively normal older adults (Chiang et al, 2017).…”
Section: Ferroptosismentioning
confidence: 99%
“…In vivo GSH quantitation using conventional magnetic resonance spectroscopy (MRS) pulse sequence (such as Point‐RESolved spectroscopy [PRESS]) in the brain is challenging and ambiguous due to spectral proximity of CH 2 peak of Cys (from GSH) with high amplitude creatine (Cr) peak (Duffy et al, ; Govindaraju, Young, & Maudsley, ; Mandal, ; Suri et al, ). The advanced spectral editing MEscher–GArwood‐PRESS (MEGA‐PRESS) (Terpstra et al, ) pulse sequence has facilitated immensely for selective in vivo GSH detection (Mandal et al, ; Terpstra et al, ; Trabesinger, Weber, Duc, & Boesiger, ) and subsequent quantitation by advanced techniques (Chiang et al, ; Mandal, Saharan, Tripathi, & Murari, ). Moreover, a recent multicenter study on healthy young controls from different continents has also shown that in vivo GSH exists in two different forms, that is, closed (GSH cl ) and extended (GSH ex ) (Mandal et al, 2017), and both can be detected with specific experimental settings using MEGA‐PRESS sequence (Shukla et al, ; Shukla, Tripathi, & Mandal, ).…”
Section: Introductionmentioning
confidence: 99%